High-durability fuel cell catalyst and preparation method thereof

By adding urea to the preparation process of fuel cell catalyst and forming a platinum nitride carbon catalyst, the problem of insufficient durability of the catalyst during frequent loading operations is solved, and a higher active area and better durability are achieved.

CN119833658APending Publication Date: 2025-04-15ZHEJIANG TIANNENG HYDROGEN ENERGY TECH CO LTD

Patent Information

Application Number
CN202411845003.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing fuel cell catalysts have insufficient durability during frequent load-changing operations, resulting in reduced catalyst active sites and degradation of cell performance.

Method used

By adding urea during the preparation of the Pt/C catalyst, and calcining of inert gas and treating acid aqueous solution at high temperature, a platinum nitride carbon catalyst (PtN/C) is formed to inhibit the agglomeration of platinum particles and improve the durability of the catalyst.

Benefits of technology

It significantly improves the durability and active area of ​​the catalyst, delays the decline of battery performance, and especially shows better durability after 30,000-turn square wave acceleration durability test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833658A_ABST
    Figure CN119833658A_ABST
Patent Text Reader

Abstract

The invention discloses a high-durability fuel cell catalyst and a preparation method thereof, and relates to the technical field of catalysts. The Pt / C catalyst is prepared first, then urea is added, nitrogen is introduced, agglomeration of platinum particles is inhibited, and the durability of the catalyst is remarkably improved; experiments prove that the catalyst prepared by the invention has higher active area (91.75 m < 2 > / gPt) and initial activity, and after 30,000 circles of square wave acceleration durability, the voltage attenuation under the same current density is 2-13mV lower than that under a contrast, and the catalyst shows better durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a high-durability fuel cell catalyst and a preparation method thereof. Background Art

[0002] Fuel cells, as an efficient and environmentally friendly electric energy conversion device, directly convert the Gibbs free energy in the chemical energy of the fuel into electrical energy through electrochemical reactions. This process is not limited by the Carnot cycle in traditional thermodynamics, thus achieving higher energy conversion efficiency. Compared with traditional internal combustion engines or pure electric vehicles, fuel cell electric vehicles (FCEVs) have shown significant advantages, including shorter refueling time, longer driving range, good working performance in low temperature environments, and zero emissions. These advantages make fuel cell technology have broad application prospects in many fields such as automobiles, airplanes, trains and other means of transportation, as well as fixed power stations, and become a key force in promoting the green and sustainable development of the automotive industry.

[0003] Among the many components of a fuel cell, the cathode oxygen reduction reaction (ORR) plays a vital role. However, this reaction process is often accompanied by a high overpotential (usually in the range of 300-400mV), resulting in a slow kinetic reaction rate, which becomes one of the key factors restricting the performance improvement of fuel cells. Therefore, as the core component of the fuel cell stack, the optimization of the performance of the catalyst is of decisive significance for improving the overall reaction efficiency of hydrogen fuel cells.

[0004] At present, Pt-based precious metal catalysts are widely used in the field of hydrogen fuel cells, among which platinum-carbon (Pt / C) catalysts are regarded as the industry standard due to their good catalytic activity, stability and conductivity. Pt / C catalysts effectively promote the ORR reaction by providing a large number of active sites, thereby improving the output power and efficiency of fuel cells. However, in actual operation, fuel cells will frequently change load according to changes in power demand. This dynamic process poses a severe challenge to the stability of the catalyst.

[0005] Specifically, frequent power changes will lead to continuous oxidation / reduction cycles on the surface of the platinum catalyst, which not only accelerates the agglomeration of Pt particles, but also may lead to the loss of Pt elements in the catalyst. Over time, the electrochemical reaction area of ​​the catalyst gradually decreases, and the number of active sites decreases sharply, which in turn causes a significant decline in battery performance. This problem has seriously restricted the commercialization of fuel cell technology, especially in the field of fuel cell vehicles, where performance decline is directly related to the service life of the vehicle, maintenance costs, and consumer acceptance.

[0006] The patent application with publication number CN115799533A discloses a platinum-based catalyst, its preparation method and application. The preparation method of the platinum-based catalyst comprises the following steps: calcining a platinum-based catalyst precursor; the platinum-based catalyst precursor comprises urea, a carbon source and a platinum salt; the mass ratio of urea to the carbon source is 1: (0.5-2). In the preparation method of the platinum-based catalyst of the present invention, urea is added, which has a protective effect on the growth of nanoparticles under high temperature decomposition, effectively inhibits the agglomeration of platinum-based catalyst particles, and thus has a significant improvement effect on the activity of the ORR reaction. However, the application does not address how to improve the durability of fuel cell catalysts. Summary of the invention

[0007] The present invention aims at the above-mentioned deficiencies existing in the fuel cell catalyst technology and provides a high-durability fuel cell catalyst and a preparation method thereof.

[0008] In one aspect, the present invention provides a method for preparing a high-durability fuel cell catalyst, comprising the following steps:

[0009] (1) Preparing a Pt / C catalyst using a platinum salt precursor and a carbon support as raw materials;

[0010] (2) mixing the Pt / C catalyst prepared in step (1) with a urea solution and drying to obtain a mixture;

[0011] (3) calcining the mixture at a high temperature under an inert gas to obtain a pyrolysis product;

[0012] (4) adding the pyrolysis product to an acidic aqueous solution and stirring, then filtering, washing to neutrality, and drying to obtain the high-durability fuel cell catalyst.

[0013] Furthermore, in step (1), the preparation method of the Pt / C catalyst comprises:

[0014] (1.1) Dispersing a platinum salt precursor uniformly in a mixed solution of nitric acid and ethanol, heating to 90-100° C. under an inert gas, and refluxing for 2-8 hours to obtain a platinum salt precursor solution;

[0015] (1.2) dispersing the carbon support in a nitric acid solution, then adding the platinum salt precursor solution according to a Pt / C catalyst platinum loading of 30-60 wt%, then adding a reducing agent, heating to 90-100° C., and reflux for 2-8 h to obtain a product;

[0016] (1.3) The product is filtered, washed and dried to obtain the Pt / C catalyst.

[0017] Preferably, in step (1), the platinum salt precursor is dinitrosodiammine platinum, and the carbon carrier is carbon black. The model of the carbon black can be selected from EC300J, BP2000 and Vulcan XC72, etc.

[0018] Preferably, in step (2), the mass ratio of the added Pt / C catalyst to the urea in the urea solution is 1:2-2:1. The present invention first prepares the Pt / C catalyst by the ethanol method, and then adds urea. The introduction of nitrogen element inhibits the agglomeration of platinum particles and significantly improves the durability of the catalyst. At the same time, the combination of nitrogen and platinum reduces the adsorption binding energy of oxygen-containing species and improves the catalytic activity of ORR.

[0019] Preferably, in step (3), the conditions for high temperature calcination are: heating to 400-600° C. at a rate of 5-10° C. / min and calcining for 2-5 h.

[0020] Specifically, in step (4), the acidic aqueous solution is hydrochloric acid, sulfuric acid or nitric acid solution, the concentration is 0.5-2M, the stirring time is 1-5h, and the drying method is vacuum drying or natural drying.

[0021] The drying method is vacuum drying, the vacuum drying temperature is 60-80° C., and the drying time is 8-10 hours.

[0022] On the other hand, the present invention also provides a high-durability fuel cell catalyst prepared by the preparation method.

[0023] Beneficial effects of the present invention:

[0024] The present invention adopts a simpler Pt / C catalyst nitridation post-treatment method, which maintains a high yield without affecting the catalyst structure, thereby maintaining a high specific surface area and excellent electrical conductivity. The introduction of nitrogen element inhibits the agglomeration of platinum particles and significantly improves the durability of the catalyst. Experiments have shown that the catalyst prepared by the present invention has a higher active area (91.75m 2 / g Pt ) and initial activity, and after 30,000 cycles of square wave acceleration endurance, the performance attenuation is smaller, showing better durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The figure is a flow chart of the preparation of the fuel cell catalyst of the present invention.

[0026] Figure 2 This is the CV curve of the fuel cell catalyst in the acidic electrolyte solution.

[0027] Figure 3This is a polarization curve diagram of a fuel cell catalyst in a membrane electrode assembly (MEA).

[0028] Figure 4 This is a diagram showing the durability performance of the fuel cell catalyst after 30,000 cycles of accelerated stress test (AST) in MEA. DETAILED DESCRIPTION

[0029] The preparation flow chart of the fuel cell catalyst of the present invention is as follows Figure 1 The specific preparation process is shown in the following examples.

[0030] Example 1

[0031] (1) Add 0.88 g HNO to 1.2 g carbon black EC300J at a mass ratio of 1:2. 3 solution (the concentration of nitric acid solution is 68wt%); hydrothermally react at 150°C for 3h, filter and wash to obtain a pretreated carbon carrier;

[0032] (2) Disperse 2 g of dinitrodiammine platinum in 165 mL of HNO 3 (concentration of 0.1 M) solution, and add 50 mL of anhydrous ethanol, react at 100 ° C for 3 h under nitrogen protection to obtain a pretreated platinum salt precursor solution;

[0033] (3) adding the pretreated carbon support to the precursor solution at a catalyst platinum loading of 50 wt%, adding anhydrous ethanol, heating to 100° C., keeping the temperature under reflux for 7 h, filtering and washing the obtained product, and vacuum drying at 80° C. for 6 h to obtain a Pt / C catalyst;

[0034] (4) 0.25 mg of urea was dissolved in a beaker containing 5 mL of deionized water, and a Pt / C catalyst and urea mass ratio of 2:1 was added, and the mixture was stirred and evaporated to dryness at 60° C. to obtain a mixture powder;

[0035] (5) The obtained mixed powder was placed in a tube furnace and N 2 , heating to 400°C at a rate of 10°C / min, and treating at 400°C for 2h to obtain a pyrolysis product;

[0036] (6) The pyrolysis product was added to an aqueous solution containing 1 M hydrochloric acid and stirred for 3 h, filtered, and washed with deionized water until the filtrate pH = 7. The filter cake was then placed in a vacuum oven at 80° C. and dried for 8 h to obtain a PtN / C catalyst.

[0037] Example 2

[0038] (1) Add 0.75 g HNO to 1 g of carbon black EC300J at a mass ratio of 1:2. 3 solution (the concentration of nitric acid solution is 68wt%); hydrothermally react at 150°C for 3h, filter and wash to obtain a pretreated carbon carrier;

[0039] (2) Disperse 2 g of dinitrodiammine platinum in 165 mL of HNO 3 (concentration of 0.1 M) solution, and add 50 mL of anhydrous ethanol, react at 100 ° C for 3 h under nitrogen protection to obtain a pretreated platinum salt precursor solution;

[0040] (3) adding the pretreated carbon support to the precursor solution at a catalyst platinum loading of 50 wt%, adding anhydrous ethanol, heating to 100° C., keeping the temperature under reflux for 7 h, filtering and washing the obtained product, and vacuum drying at 80° C. for 6 h to obtain a Pt / C catalyst;

[0041] (4) 0.25 mg of urea was dissolved in a beaker containing 5 mL of deionized water, and a Pt / C catalyst and urea mass ratio of 2:1 was added, and the mixture was stirred and evaporated to dryness at 60° C. to obtain a mixture powder;

[0042] (5) The obtained mixed powder was placed in a tube furnace and N 2 , heating to 600°C at a rate of 10°C / min, and treating at 600°C for 2h to obtain a pyrolysis product;

[0043] (6) The pyrolysis product was added to an aqueous solution containing 1 M hydrochloric acid and stirred for 3 h, filtered, and washed with deionized water until the filtrate pH = 7. The filter cake was then placed in a vacuum oven at 80° C. and dried for 8 h to obtain a PtN / C catalyst.

[0044] Comparative Example 1

[0045] (1) Add 0.88 g HNO to 1.2 g carbon black EC300J at a mass ratio of 1:2. 3 solution (the concentration of nitric acid solution is 68wt%); hydrothermally react at 150°C for 3h, filter and wash to obtain a pretreated carbon carrier;

[0046] (2) Disperse 2 g of dinitrodiammine platinum in 165 mL of HNO 3 (concentration of 0.1 M) solution, and add 50 mL of anhydrous ethanol, react at 100 ° C for 3 h under nitrogen protection to obtain a pretreated platinum salt precursor solution;

[0047] (3) adding the pretreated carbon support to the precursor solution at a catalyst platinum loading of 50 wt%, adding anhydrous ethanol, heating to 100° C., keeping the temperature under reflux for 7 h, filtering and washing the obtained product, and vacuum drying at 80° C. for 6 h to obtain a Pt / C catalyst;

[0048] Comparative Example 2

[0049] Commercial Pt / C catalyst.

[0050] Comparative Example 3

[0051] (1) Add 0.75 g HNO to 1 g of carbon black EC300J at a mass ratio of 1:2. 3 solution (the concentration of nitric acid solution is 68wt%); hydrothermally react at 150°C for 3h, filter and wash to obtain a pretreated carbon support;

[0052] (2) 0.52 g H 2 PtCl 6 , 0.25g urea is evenly dispersed in 1L H 2 O to obtain a Pt salt precursor solution;

[0053] (3) adding the pretreated carbon support to the precursor solution at a catalyst platinum loading of 50 wt%, stirring and refluxing at 80° C. for 7 h, filtering and washing the obtained product, and vacuum drying at 80° C. for 6 h to obtain a catalyst precursor;

[0054] (5) Place the obtained catalyst precursor powder in a tube furnace and introduce N 2 , heating to 600°C at a rate of 10°C / min, and treating at 600°C for 2h to obtain a pyrolysis product;

[0055] (6) The pyrolysis product was added to an aqueous solution containing 1 M hydrochloric acid and stirred for 3 h, filtered, and washed with deionized water until the filtrate pH = 7. The filter cake was then placed in a vacuum oven at 80° C. and dried for 8 h to obtain a PtN / C catalyst.

[0056] Test Example 1

[0057] The catalysts prepared in the examples and comparative examples were respectively subjected to acidic ORR performance tests, and the ORR performance test method was as follows: 1. Accurately weigh 5 mg of the catalyst; 2. Add 2 mL of water, 2 mL of isopropanol, and 20 μL of Nafion D520 solution (5%) in sequence, and ultrasonically treat for 1 h to obtain a uniformly mixed catalyst ink; 3. Take 5 μL of the dispersed ink and drip it evenly on the glassy carbon disk electrode twice, let it dry naturally at room temperature, and use it as the working electrode, and use a saturated calomel electrode (SCE) and a platinum sheet as the reference electrode and the counter electrode, respectively; 4. Place the electrodes in an electrolytic cell to form a three-electrode system; the electrolyte is N2 Saturated 0.5 M H 2 SO 4 To further verify the performance of the catalyst MEA, the catalyst slurry was coated on both sides of the proton membrane to obtain the MEA, and the MEA was subjected to a single cell polarization test and a durability test under the same conditions. The test conditions are shown in Table 1 and Table 2:

[0058] Table 1. Single cell polarization conditions

[0059] Battery reaction temperature 80℃ Relative humidity of reaction gas Anode: 80% RH; Cathode: 100% RH Reaction gas flow <![CDATA[St H 2 :1L / min;St Air:2L / min]]> Outlet back pressure 150kPa Each electrical test time 1.5min

[0060] Table 2. Single cell durability test conditions

[0061]

[0062] Table 3 ECSA values ​​of fuel cell catalysts in acidic electrolyte solutions

[0063] catalyst <![CDATA[ECSA(m 2 / g Pt )]]> Example 1 82.16 Example 2 91.75 Comparative Example 1 75.48 Comparative Example 2 63.72 Comparative Example 3 79.69

[0064] Test results such as Figure 2-4 As shown in Table 3, the combination of nitrogen and platinum reduces the adsorption energy of the catalyst to oxygen-containing intermediates and improves the catalyst activity. The presence of the Pt-N bond makes the catalyst less likely to dissolve during the cycle. Compared with the comparative example, the catalyst of the embodiment has a higher active area (91.75m 2 / g Pt ) and initial activity, and after 30,000 cycles of square wave accelerated durability, the voltage decay at the same electrical density is 2-13mV smaller than that of the control group, showing better durability performance.

Claims

1. A method for preparing a high-durability fuel cell catalyst, characterized in that: The following steps are involved: (1) Preparing a Pt / C catalyst using a platinum salt precursor and a carbon support as raw materials; (2) mixing the Pt / C catalyst prepared in step (1) with a urea solution and drying to obtain a mixture; (3) calcining the mixture at a high temperature under an inert gas to obtain a pyrolysis product; (4) adding the pyrolysis product to an acidic aqueous solution and stirring, then filtering, washing to neutrality, and drying to obtain the high-durability fuel cell catalyst.

2. The method for preparing a high-durability fuel cell catalyst according to claim 1, characterized in that: In step (1), the preparation method of the Pt / C catalyst comprises: (1.1) Dispersing a platinum salt precursor uniformly in a mixed solution of nitric acid and anhydrous ethanol, heating to 90-100° C. under an inert gas, and refluxing for 2-8 hours to obtain a platinum salt precursor solution; (1.2) dispersing the carbon support in a nitric acid solution, then adding the platinum salt precursor solution according to a Pt / C catalyst platinum loading of 30-60 wt%, then adding a reducing agent, heating to 90-100° C., and reflux for 2-8 h to obtain a product; (1.3) The product is filtered, washed and dried to obtain the Pt / C catalyst.

3. The method for preparing a high-durability fuel cell catalyst according to claim 1, characterized in that: In step (1), the platinum salt precursor is dinitrosodiammine platinum, and the carbon carrier is carbon black.

4. The method for preparing a high-durability fuel cell catalyst according to claim 1, characterized in that: In step (2), the mass ratio of the Pt / C catalyst added to the urea in the urea solution is 1:2-2:

1.

5. The method for preparing a high-durability fuel cell catalyst according to claim 1, characterized in that: In step (3), the high temperature calcination conditions are: heating to 400-600°C at a rate of 5-10°C / min and calcining for 2-5h.

6. The method for preparing a high-durability fuel cell catalyst according to claim 1, characterized in that: In step (4), the acidic aqueous solution is hydrochloric acid, sulfuric acid or nitric acid solution, the concentration is 0.5-2M, and the stirring time is 1-5h. The drying method is vacuum drying or natural drying.

7. The method for preparing a high-durability fuel cell catalyst according to claim 6, characterized in that: The drying method is vacuum drying, the vacuum drying temperature is 60-80° C., and the drying time is 8-10 hours.

8. A high-durability fuel cell catalyst prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Platinum-based catalyst as well as preparation method and application thereof

    CN115799533A

Cited By

  • Aperture-adjustable sulfur-nitrogen co-doped mesoporous carbon material for fuel cell

    CN121974326A